Subscribers’ Attitude towards Direct Mail Infiltration from Unknown Sources - Chinwendu, Okonkwo Deborah; Chinwuba, Moguluwa Shedrach (International Journal of Marketing Research Innovation, 2018)
Purpose – The study was carried out to describe individuals’ outlook by unearthing inherent dispositions assumed as a result of indiscriminate influx of unwanted mails directly into subscribers’ mobile devices from unscrupulous service providers, which eventually results into certain attitudes that may be either positive or negative. The study was directed towards determining subscribers’ general reaction towards direct mail infiltration from unknown sources and their resulting attitude; and also ascertaining whether they view these mails as an invasion of their privacy.Design/methodology/approach – The paper adopted the descriptive research design, and used the survey method to gain an understanding into individuals’ outlook towards unsolicited text messages. 114 copies of the structured questionnaire were distributed to individuals who own a mobile phone within the Enugu metropolis, Nigeria. Respondents were purposively selected as only mobile phone owners who are educated were deemed eligible for the study. A total of 82 usable copies of the questionnaire were analysed using frequencies, percentages and the one-sample t-test statistic was used to test the hypotheses.Findings – The results show that subscribers have a distaste for unsolicited text messages and therefore react unfavourably, as most of them would either delete the messages the moment they are identified as unwanted, or delete them immediately after reading them. This inadvertently brings about the formation of a negative attitude towards unsolicited direct mails generally . It further reveals that the influx of unsolicited text messages during odd hours is a breach of ethical standards as regards to privacy. Consequently, individuals prefer that their consent be sought first by service providers before bombarding them with those mails.Practical implications – This paper addresses an important issue affecting individuals in this information age. As the spread of information becomes more rapid, certain areas of concern arise. This paper addresses those areas especially with respect to privacy matters as a way of emphasizing the significance of ethics in what is supposed to be an ordered system.Originality/Value – The novelty of this paper is evident in its demonstration of individuals’ innate feelings and its exposition of inherent attitude patterns in a setting where ethics is undermined. It utilizes the opinions gathered to elucidate the need for more cultured patterns of self-expression and communicating to others.